A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China - Zeng, Zhao-Chi; Zhao, Jian; Chen, Chun-Quan; Chen, Guo-Ling; Zhang, Zhong; Wang, Ying-Yong (Zootaxa, 2017)
A new species, Gracixalus jinggangensis sp. nov., is described based on a series of specimens collected from Mount Jinggang, Jiangxi Province, southeastern China. The new species is distinguished from all other known congeners by the following combination of morphological characters: relatively small body size, SVL 27.9–33.8 mm in nine males and 31.6 mm in a single female; upper eyelid and dorsum lacking spines; skin of dorsal and lateral surface of head, body and limbs rough with sparsely scattered with tubercles; ventral skin granular; tibiotarsal projection absent; finger webbing rudimentary; toes with moderately developed webbing; brown to beige above in life, with an inverse Y-shaped dark brown marking extending from the interorbital region to the middle of dorsum; males with a single, subgular vocal sac, barely visible nuptial pads with minute granules on the dorsal surface of the bases of first and second fingers. The new species is also genetically divergent from all other Gracixalus for which comparable 16S rRNA gene sequences are available. The discovery of Gracixalus jinggangensis sp. nov. represents the twelfth known species in the genus.